'Getting there': Do we need to study how people compose music?. Issue 2 (16th February 2012) - Collins, Dave
The study of musical composition as an aspect of creative cognition remains underresearched in comparison with other facets of the musical experience such as perception and performance. This short position article questions why this might be the case and any associated implications for music education. As a foil to lingering Romantic and post-Romantic notions of creativity as unexplorable 'inspiration', it posits a stance of viewing the act of musical composition (in terms of 'getting there' from silence to a sound object) as one aspect of human problem-solving that can be interrogated through a research methodology that circles around verbal protocol analysis.